Novel Gastroretentive Controlled Release Formulations for Once-Daily Administration: Assessment of Clinical Feasibility and Formulation Concept for Raltegravir. (November 2016) - Krishna, Rajesh; Rizk, Matthew L.; Larson, Patrick J.; Schulz, Valerie; Friedman, Evan; Gupta, Pranav; Kesisoglou, Fillippos; Connor, Alyson; McDermott, John; Smith, Ronald; Evans, Philip
Background: Raltegravir is an integrase strand transfer inhibitor indicated in combination with other anti-retroviral medicinal products for the treatment of HIV-1 infection, given twice daily. Although a BCS class II compound, raltegravir exhibits low colonic absorption, thus making development of modified release formulations challenging. It was hypothesized that a gastroretentive (GR) formulation would increase trough (C24 h ) concentrations of raltegravir, hence being amenable to a once-daily (QD) regimen. Methods: Iterative prototype GR formulations were developed in monolithic, bilayer, and trilayer tablet designs. Four phase I studies in healthy subjects were conducted to provide proof of formulation concept. Results: Raltegravir C24 h was increased by a GR formulation with scintigraphy data supporting gastric retention. Single-dose exposures from a trilayer tablet administered in the morning with a high-fat meal resulted in acceptable C24 h values. However, C24 h values for evening dosing with a high-fat meal did not meet the success criteria for QD administration. Raltegravir C24 h and area under the curve (AUC) values after AM dosing with a low-fat meal were significantly lower than after dosing with a moderate-fat meal. Skipping, delaying, or giving a low-fat, low-calorie lunch after dosing with a high-calorie breakfast also resulted in an unacceptable decline in C24 h values. The requirements for consistent product performance under varying conditions of diet, timing of dosing, and dose were not favorable when given as GR tablets. Conclusions: The findings from these studies offer valuable insights into modifying the absorption of candidate drugs with limiting colonic permeability and solubility characteristics and the interplay between meal, dose timing, and GR formulation performance.